Effects of Cirsium japonicum var. maackii on avelliation of metabolic disease by improving insulin resistance - Hye-Bin Yoon; Yuseong Jang; Hyeon-Gi Paik; Hwal Choi; Jihye Choi; Jungkee Kwon (Laboratory Animal Research)
Abstract Background Metabolic syndrome (MetS) refers to a group of risk factors that cause health problems, such as obesity, diabetes, dyslipidemia, and hyperglycemia. MetS is characterized by insulin resistance, which leads to abnormal insulin sensitivity. Cirsium japonicum var. maackii (CJ) is perennial herbaceous species found in Asia that exhibits antioxidant, antidiabetic, antitumor, antifungal, and anti-inflammatory activities. In this study, we aimed to measure the effects of CJ on MetS by improving insulin resistance in a db/db type 2 diabetes mouse model. After administrating CJ extract (CJE) for db/db mouse for 6 weeks, we measured with the evaluation of Insulin resistance, lipid profiles, histological analysis of liver, damage of liver and kideny. Results The results showed that CJE was effective in reducing body weight and fat mas and showed a positive effect on lowering blood glucose and improving insulin sensitivity. CJE improved dyslipidemia by increasing serum-HDL levels and decreasing serum-LDL levels. In addition, CJE reduced liver and kidney damage in histological analysis. Conclusions These results demonstrate the anti-diabetic effects of CJE and suggest its potential for improving MetS. Therefore, CJE may have potential values as a functional food material for managing MetS.